Methane production: Where should we focus our attention? - Committee, Editorial (Austral Journal of Veterinary Sciences, 2020)
The UN recently called for reducing meat consumption due to its contribution to global warming. However, from my perspective as a researcher, the role of livestock greenhouse gas emissions is often exaggerated. The annual reports of greenhouse gas (GHG) emissions from the EU and the USA reveal that ...